2014
DOI: 10.1007/s12011-014-9952-4
|View full text |Cite
|
Sign up to set email alerts
|

Could Selenium Administration Alleviate the Disturbances of Blood Parameters Caused by Lithium Administration in Rats?

Abstract: Lithium is widely used in medicine, but its administration can cause numerous side effects. The present study aimed at the evaluation of the possible application of selenium, an essential and antioxidant element, as a protective agent against lithium toxicity. The experiment was performed on four groups of Wistar rats: I (control)—treated with saline, II (Li)—treated with lithium (Li2CO3), III (Se)—treated with selenium (Na2SeO3) and IV (Li + Se)—treated with lithium and selenium (Li2CO3 and Na2SeO3) in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
6
14
1
Order By: Relevance
“…Although the majority of the observed changes were insignificant, co-administration of selenium seems to display a tendency to restoration action in the case of parameters slightly altered by lithium alone (GPx after 3 weeks and the other studied parameters after 6 weeks). The obtained results are consistent with those obtained in our previous study in blood (Kiełczykowska et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Although the majority of the observed changes were insignificant, co-administration of selenium seems to display a tendency to restoration action in the case of parameters slightly altered by lithium alone (GPx after 3 weeks and the other studied parameters after 6 weeks). The obtained results are consistent with those obtained in our previous study in blood (Kiełczykowska et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study the total mean of serum urea in different doses of lithium carbonate and L-ascorbic acid showed higher values compared to the control group. The results agreed with Kielczykowska M, et al reported that lithium carbonate and L-ascorbic acid co administration treated rats in the form of water solution by stomach tube for 6 weeks caused the increased serum urea [22]. A similar study done by Omar HE, et al who reported that different doses of lithium carbonate and antioxidants vitamin treated rats showed increase of urea levels in all treated groups [23].…”
Section: Discussionsupporting
confidence: 86%
“…A similar study done by Sharma S, et al reported that lithium therapy treatment in rats caused increased urea [2]. The results also agree Kielczykowska M, et al Modawe reported that lithium carbonate treated rats in the form of water solution by stomach tube for 6 weeks caused the increased serum urea [22]. A similar study conducted by Omar HE, et al reported that different doses of lithium carbonate treated rats showed increase in all groups treated.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the previous part of our research, we found that lithium treatment significantly decreased serum Mg and enhanced serum Ca [23]. In contrast, in the current study, magnesium in organs was not affected by Li treatment, whereas calcium was changed in the studied organs in different ways.…”
Section: Discussioncontrasting
confidence: 81%